Reciprocal recurrent selection for grain yield in two varieties of maize - Lee, C. H.; Yap, T. C. (Faculty of Agriculture, University of Malaya, 1975)
A reciprocal recurrent selection programme was initiated to improve the yield of Local Flint and Metro varieties. Results of one cycle of selection showed significant improvement in grain yield of both populations while the coefficient of variation values for most characters decreased in Local Flint but increased in Metro. Increase in grain yield of Local Flint was correlated with increase in ear length, ear diameter, number of rows per ear, number of kernels per row and silking date. In the case of Metro, increase in grain yield was accompanied by increases in all the agronomic characters.